Meningkatkan hasil belajar peserta didik dengan menggunakan model pembelajaran berbasis proyek (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This Study aims to find Project Based Learning Quality to increase Mathematics Learning results.  The Population of this study is 247 students from VIII class. Then, the sample of this study using 68 Students from VIII-1 dan VIII-2 Class Junor High School of Tanjung Morawa.  I got it using Cluster Random Sampling Method. In this case, the author using –t-test as the analysis. We got that: 1) Project Based Learning to increase the results of student’s mathematic. 2) Student’s grades in math almost 79,47 after using the Project-based Learning Model.  The value has increased than ever before 61,35. 3) Project-based learning has an impact on student’s learning. This study described that quality results of a student’s learning in math using Project Based Learning depend on the procedure applied by teacher.
Keywords: hasil belajar; pembelajaran berbasis proyek